2023
DOI: 10.1097/md.0000000000033957
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between NLR, NHR, and clinicopathological characteristics, and prognosis of acute ischemic stroke

Abstract: Neuroinflammation plays an essential role in the process of acute ischemic stroke (AIS) injury repair. The current study seeks to investigate the relationship between the neutrophil/lymphocyte ratio (NLR) and neutrophil/high-density lipoprotein cholesterol ratio (NHR) and AIS disease severity and short-term prognosis. As such, the primary aim of this study is to improve AIS diagnosis and treatment. A total of 136 patients with AIS at the Nantong Third People’s Hospital were retrospectively analyzed. The inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Meanwhile, Sadeghi et al have found that a high NLR-low LMR (lymphocyte-monocyte ratio) combination as observed at 24 h after thrombolysis can serve as an independent predictor of 3-months poor outcome in AIS patients [ 21 ]. Studies have also shown that high baseline NLR is an independent risk factor for poor prognosis in early neurodegenerative AIS [ 22-24 ]. To date, NLR is a reliable prognostic marker for AIS, and its prognostic value has been fully proven.…”
Section: Effect Of Blood Biomarkers On Prognosis Of Aismentioning
confidence: 99%
“…Meanwhile, Sadeghi et al have found that a high NLR-low LMR (lymphocyte-monocyte ratio) combination as observed at 24 h after thrombolysis can serve as an independent predictor of 3-months poor outcome in AIS patients [ 21 ]. Studies have also shown that high baseline NLR is an independent risk factor for poor prognosis in early neurodegenerative AIS [ 22-24 ]. To date, NLR is a reliable prognostic marker for AIS, and its prognostic value has been fully proven.…”
Section: Effect Of Blood Biomarkers On Prognosis Of Aismentioning
confidence: 99%
“…According to some studies, stroke registers a prevalence of over 100 million cases worldwide, with about 12.2 million new cases of strokes every year and a mortality of about 6.55 million per year [ 2 , 3 ]. In addition to the high number of deaths, stroke causes about five million cases of permanent disability annually [ 4 ]. Statistics show that stroke is currently the second leading cause of death and the third major cause of disability globally [ 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%